Student-Led Classes and Group Work: A Methodology for Developing Generic Skills - Alison Greig (Legal Education Review)
While the use of small to medium-sized seminar-style groups has long been a feature of some Australian law faculties, such as the University of New South Wales, it is a recent innovation in others, including the University of Western Australia and the University of Adelaide. In March 1996 the Faculty of Law at the University of Sydney made a decision to move from a traditional lecture and tutorial structure to seminar- style classes of limited size. This article discusses the reasons for the move away from a traditional lecture/tutorial format to an interactive seminar-style model of teaching. The paper explains the 1999 review of the new model and presents highlights of the review. It provides an opportunity to reflect on both the shift in teaching paradigm and the means of assessing such broad-based program shifts. At the time the review was completed the model had been in operation for three years.